2002
DOI: 10.1210/en.2002-220598
|View full text |Cite
|
Sign up to set email alerts
|

In Altering the Release of Glucocorticoids, Ketorolac Exacerbates the Effects of Systemic Immune Stimuli on Expression of Proinflammatory Genes in the Brain

Abstract: Nonsteroidal antiinflammatory drugs (NSAIDs) are widely used for their antiinflammatory, antipyretic, and analgesic properties. The molecular basis for the therapeutic action of NSAIDs is believed to be in their ability to inhibit cyclooxygenase (COX) activity and thereby blocking the production of prostaglandins. Emerging evidence now suggests that NSAIDs can exert their pharmacological effects through other mechanisms. This study investigated the influence of a nonselective COX-inhibitor ketorolac on IL-1bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…EPA effects of IL-1-induced changes in DA and PLA2 C Song et al neurotransmitters and metabolites was significantly changed, and IL-1-induced mRNA expressions related to PGE2, glucocorticoids and inflammation in the brain also occurred) (Song et al, 1999;Blais et al, 2002;Zhang and Rivest, 2000). Following decapitation, blood was collected and serum samples were used to measure corticosterone concentrations.…”
Section: Experimental Designmentioning
confidence: 99%
“…EPA effects of IL-1-induced changes in DA and PLA2 C Song et al neurotransmitters and metabolites was significantly changed, and IL-1-induced mRNA expressions related to PGE2, glucocorticoids and inflammation in the brain also occurred) (Song et al, 1999;Blais et al, 2002;Zhang and Rivest, 2000). Following decapitation, blood was collected and serum samples were used to measure corticosterone concentrations.…”
Section: Experimental Designmentioning
confidence: 99%
“…Systemic administration of COX inhibitors indomethacin, ketoralac or NS-398 prior to LPS or IL1b challenges abrogates these responses. 11,37-40 COX inhibition prevents activation of PVN neurons and its afferent pathways in response to proinflammatory cytokines and LPS, 41,42 while intracerebral administration of PGE 2 stimulates these neuronal circuits and plasma ACTH and corticosterone release. [43][44][45] Moreover, both COX-2 and mPGES-1 are rapidly upregulated by circulating immune ligands 4,5,14,15,20,22,23,46 and COX-2-and mPGES-1-deficient mice do not develop fever in response to circulating LPS.…”
Section: Discussionmentioning
confidence: 99%
“…However, DEX is able to repress lipopolysaccharide (LPS)-induced NF-kB activation in the brain [22], and exogenous Cort can abolish stimulated IL-1b and TNF-a gene expression in microglial cells [23]. Recently, it was demonstrated that systemic pretreatment with endotoxin is able to abolish the strong and time-dependent transcriptional activation of inflammatory genes in microglial cells ipsilateral to the site of LPS intrastriatal injection.…”
Section: Discussionmentioning
confidence: 99%